Computer-aided Analysis of Thermal Convection near Electric Devices - Czapp, S.; Czapp, M. (Elektronika ir Elektrotechnika, 2011)
Current-carrying capacity of electric devices strictly depends on the heat transfer between electric devices and surroundings. For example, in order to increase the current-carrying capacity of devices, a forced circulation of air is applied. Comprehensive observation and analysis of natural thermal convection indicates that the process intensity depends on positioning of the electric devices and addi-tional elements as screens or canals close to the device. In the paper analysis of thermal convection with the use of Ansys/Flotran code is presented. The results of the analysis of thermal convection with the use of additional screen close to the electric device are pre-sented. Optimum distance between the electric device and the screen is evaluated. Ill. 8, bibl. 8 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.109.3.163